Reduced emotional stress reactivity to a real-life academic examination stressor in students participating in a 20-week aerobic exercise training: A randomised controlled trial using Ambulatory Assessment. (September 2015) - von Haaren, Birte; Haertel, Sascha; Stumpp, Juergen; Hey, Stefan; Ebner-Priemer, Ulrich
Abstract: Objectives: To examine if a preventive 20-week aerobic exercise intervention (AET) can improve emotional stress reactivity during real-life stress. Design: Randomised controlled trial; within-subject design. Method: Sixty-one inactive students were randomly assigned to a waiting control and an AET group. To capture the situation-specific, intra-individual data in real life, electronic diaries were used. Participants reported their moods and perceived stress (PS) repeatedly over two days during their daily routines pre- and post-intervention. The pre-intervention baseline assessment was scheduled at the beginning of the semester, and the post-intervention assessment was scheduled at a real-life stressful episode, an academic examination. For the aerobic fitness assessment, both groups completed a cardiopulmonary exercise test on the treadmill before and after the intervention. Multilevel models (MLMs) were conducted to compare within- and between-subject associations. Results: Significant emotional stress reactivity was evident in both groups during all assessment periods. However, participants in the AET group showed lower emotional stress reactivity compared with their control counterparts after the 20-week training programme during the real-life stress episode (the academic examination). Conclusions: AET conferred beneficial effects on emotional stress reactivity during an academic examination, which is likely an extremely stressful real-life situation for students. AET appears to be a promising strategy against the negative health effects of accumulated emotional stress reactivity. Highlights: Aerobic exercise training reduces emotional stress reactivity in real life. Exercisers show decreased NA in conditions of enhanced perceived stress. Emotional stress reactivity of exercisers is reduced at both stressful periods. Aerobic exercise appears to be a promising strategy against stress-related diseases.